Penghambatan Ekspresi Gen dengan Antisense Oligonukleotida sebagai Upaya Pengobatan Penyakit - Dian Ratih Laksmitawati; Ani Retno Prijanti (JURNAL ILMU KEFARMASIAN INDONESIA, 2005)
Due to the development of biomolecular science eg. overexpression genes, genes that cause diseases can be identfied, Based on this fact, researchers developed a therapeutic strategy by inhibiting the gene expression using oligonucleotide antisense. Therapy using oligonucleotide antisense was based on a natural process of gene expression. Specific artificial antisense will match complementary with DNA and mRNA. By this process the transcription will stop. The effort of therapy is relatively new but a few have been carried out in the clinical trial phase. Obstacles are encountered in reaching the target cell by the oligonucleotide antisense.